Carbon Labelling and Low-Income Country Exports: A Review of the Development Issues - Brenton, Paul; Edwards-Jones, Gareth; Jensen, Michael Friis (2012)
This article discusses the carbon accounting and carbon-labelling schemes being developed to address growing concerns over climate change. Its particular concern is their impact on small stakeholders, especially low-income countries. The popular belief that trade is by definition problematic is not true; carbon efficiencies elsewhere in the supply chain may more than offset emissions from transportation. Indeed, low-income countries may offer important opportunities for carbon emission reductions because of their favourable climatic conditions and use of low energy-intensive production techniques. However, their effective inclusion in labelling schemes will require innovative solutions to provide low-cost data collection and certification.